IMPLEMENTASI CYBER PUBLIC RELATIONS BADAN PERENCANAAN PEMBANGUNAN DAERAH DAN PENELITIAN PENGEMBANGAN (BAPPEDALITBANG) KOTA SAMARINDA - Oktaviany, Nur Amelia; Juwita, Rina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Cyber ​​Public Relations (CPR) is a recent innovation in public relations driven by advances in Internet technology. PR used to use traditional mass media such as television, newspapers and radio to communicate with the public. However, over time, many companies and agencies have switched to using the Internet as an advertising vehicle. This study aims to understand and improve the reputation of Bappedalitban Kota Samarinda CPR practices. The research methods used are descriptive and qualitative, collecting data through observations and interviews. Three informants were selected based on certain criteria. Data Analysis Using Interactive Analysis Techniques by Mathew B. Miles and Michael Huberman. The results of the study show that Bappedaritvan Kota Samarinda's CPR practice includes her four components of CPR. First, fact-finding shows that website and social media usage is still suboptimal and there is no PR department dedicated to it. Secondly, the plan will be carried out by actively disseminating the activities of Bape Dalit Ban in Samarinda City through its website and social media. Thirdly, communication includes his social media accounts such as Instagram, Facebook, Twitter, Youtube, Tiktok, etc., but he actively uses them, since the majority of Internet users in Samarinda City Bappedalitban are parents. Only Instagram and Facebook are. While the website only lists phone numbers as a public interaction feature, social media uses DM and comment features. Fourth, assessments are conducted by Samarinda's response team every 3 months, 6 months and 1 year. The Samarinda City Government issues awards for the openness of public information and social media activity. The implementation of CPR is expected to improve the reputation of Bappedalitban Kota Samarinda.